Stem cell therapy and its potential role in pituitary disorders. Issue 4 (August 2017) - Lara-Velazquez, Montserrat; Akinduro, Oluwaseun O.; Reimer, Ronald; Woodmansee, Whitney W.; Quinones-Hinojosa, Alfredo
Abstract : Purpose of review: The pituitary gland is one of the key components of the endocrine system. Congenital or acquired alterations can mediate destruction of cells in the gland leading to hormonal dysfunction. Even though pharmacological treatment for pituitary disorders is available, exogenous hormone replacement is neither curative nor sustainable. Thus, alternative therapies to optimize management and improve quality of life are desired. Recent findings: An alternative modality to re-establish pituitary function is to promote endocrine cell regeneration through stem cells that can be obtained from the pituitary parenchyma or pluripotent cells. Stem cell therapy has been successfully applied to a plethora of other disorders, and is a promising alternative to hormonal supplementation for resumption of normal hormone homeostasis. Summary: In this review, we describe the common causes for pituitary deficiencies and the advances in cellular therapy to restore the physiological pituitary function.